Optical line systems transmission aspects - Maclean, D. J. H (John Wiley & Sons, 1996)
This comprehensive book surveys all aspects of optical line systems and helps the telecommunications engineer stay up to date in this growing field. It offers a unique analysis of the properties of major transmission hardware components and of the design of optical fiber line systems.